Pandemic fatigue, behavioral intention and predictors of COVID-19 vaccination among individuals living with HIV in Bench Sheko Zone, in Southern Ethiopia, application of TBP: a facility based cross sectional study - Alie, Melsew Setegn; Abebe, Gossa Fetene; Negesse, Yilkal; Girma, Desalegn; Adugna, Amanuel (Frontiers in Public Health, 2024)
Introduction: People living with HIV often face inequalities and negative outcomes, which make them vulnerable. To protect this population and achieve herd immunity, it is crucial for COVID-19 vaccination efforts to prioritize and encourage vaccination among people living with HIV (PLWH). However, in Ethiopia, there is a lack of motivation in this regard. To tackle this issue, a study was conducted in the Bench Sheko Zone of Southwest Ethiopia. The study aimed to assess pandemic fatigue, behavioral intention to get vaccinated, and factors influencing COVID-19 vaccine acceptance among PLWH in that region.A facility-based cross-sectional study was conducted among individuals living with HIV who were over 18 years old in Bench-Sheko Zone, located in Southwest Ethiopia. The study included a total of 590 participants from four ART healthcare facilities within the zone. The researchers utilized the Theory of Planned Behavior to examine the predictors of intention to use preconception care. Multiple linear regression analysis was employed to determine these predictors, with a p-value of less than 0.05 considered as indicative of a significant association.The final analysis of the study involved the use of linear regression analysis, and the measure of association was presented as the standardized B coefficient following a multivariable logistic regression analysis.In the conducted study, the response rate was an impressive 98%. The researchers aimed to investigate the behavioral intention towards the COVID-19 vaccine, which was found to be 55.7%. The average age of the participants in the study was 34.65±6.67. The study was the assessment of pandemic fatigue, which had a mean value of 17.22 ±5.28. During the multivariate linear regression analysis, four predictor variables were identified. Among these, three variables, namely subjective norm, pandemic fatigue, and age, positively influenced the behavioral intention towards the COVID-19 vaccine. Comprehending these factors can assist healthcare professionals and policymakers in formulating precise interventions and strategies aimed at enhancing the acceptance and adoption of vaccines. Conclusion: The study indicates that individuals living with HIV have shown lower vaccine intention compared to previous research. The study identifies subjective norm, pandemic control measures, income, and age as predictors of individuals' intention.